Re-activate â€œentanglementsâ€ of Urban Memory Durban, a South African City (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2018)
Some specific places in Durban have been changing identity and functions throughout history and today these places can be still considered as â€œplaces of changesâ€. Durbanâ€™s precolonial origins suggests that there are cities introducing new perspectives on space, sociality and life in an African city providing a conceptual tool for shifting the interpretation from precolonial to post-apartheid Durban. The spacial and social creolisation of the pre-colonial period has left an important legacy in Durban and beyond. Any cultural analysis must thus take into account of mutuality and entanglement in these places.